Frequent mutations of genes encoding ubiquitin-mediated proteolysis pathway components in clear cell renal cell carcinoma - Guo, Guangwu; Gui, Yaoting; Gao, Shengjie; Tang, Aifa; Hu, Xueda; Huang, Yi; Jia, Wenlong; Li, Zesong; He, Minghui; Sun, Liang; Song, Pengfei; Sun, Xiaojuan; et al. (Nature genetics, 2012)
Huanming Yang, Zhiming Cai, Jun Wang and colleagues report whole-exome sequencing of 10 clear cell renal cell carcinomas followed by a screen of ~1,100 genes in a total of 98 tumors. They found 12 new disease-associated genes and detected frequent alterations in the ubiquitin-mediated proteolysis pathway. We sequenced whole exomes of ten clear cell renal cell carcinomas (ccRCCs) and performed a screen of ∼1,100 genes in 88 additional ccRCCs, from which we discovered 12 previously unidentified genes mutated at elevated frequencies in ccRCC. Notably, we detected frequent mutations in the ubiquitin-mediated proteolysis pathway (UMPP), and alterations in the UMPP were significantly associated with overexpression of HIF1α and HIF2α in the tumors ( P = 0.01 and 0.04, respectively). Our findings highlight the potential contribution of UMPP to ccRCC tumorigenesis through the activation of the hypoxia regulatory network.